2023
DOI: 10.3892/ol.2023.13859
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of surufatinib in the treatment of advanced solid tumors: a systematic evaluation and meta‑analysis

Abstract: Previous retrospective studies have suggested that surufatinib is effective for treating advanced solid tumors; however, the efficacy and safety of this drug needs to be investigated further via high-quality evidence or randomized controlled trials. In the present study, a meta-analysis was carried out to evaluate the safety and effectiveness of surufatinib for patients with advanced solid tumors. Systematic, electronic literature searches were conducted using PubMed, EMBASE, Cochrane Library and ClinicalTrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Anti-angiogenic therapy with the VEGF-targeting antibody bevacizumab has not shown clinical benefit, with or without concomitant chemotherapy [193,194]. Recent clinical trials found that multi-tyrosine kinase inhibitors have been efficacious in treating a variety of other neoplasms [195], including pancreatic neuroendocrine tumors [196], which, in contrast to PDAC, are notably hypervascular [197]. One such drug, surufatinib, impairs angiogenesis by targeting VEGFR while simultaneously blocking FGFR1 (a mechanism of resistance to anti-VEGF therapy) and CSF-1R, thereby decreasing the recruitment of tumor-associated macrophages [198].…”
Section: Vasculaturementioning
confidence: 99%
“…Anti-angiogenic therapy with the VEGF-targeting antibody bevacizumab has not shown clinical benefit, with or without concomitant chemotherapy [193,194]. Recent clinical trials found that multi-tyrosine kinase inhibitors have been efficacious in treating a variety of other neoplasms [195], including pancreatic neuroendocrine tumors [196], which, in contrast to PDAC, are notably hypervascular [197]. One such drug, surufatinib, impairs angiogenesis by targeting VEGFR while simultaneously blocking FGFR1 (a mechanism of resistance to anti-VEGF therapy) and CSF-1R, thereby decreasing the recruitment of tumor-associated macrophages [198].…”
Section: Vasculaturementioning
confidence: 99%